Modeling and Simulation of Deflected Anode Erosion in Vacuum Arcs - 王立军 黄小龙 贾申利 周鑫 史宗谦 (Plasma science & technology, 2014)
In vacuum switch devices, the connection bus bar out of the vacuum interrupter will generate a transverse magnetic field in the arc column region, and under the influence of this magnetic field, the whole arc column will deflect from the electrode center, thus leading to deflected anode erosion. In this paper, a two-dimensional deflected anode erosion model is established, anode erosions under different deflection distance are simulated and analyzed, and results of anode surface temperature, anode melting and surface evaporation flux are obtained. The simulation results show that the deflected heat flux density will lead to deflected distribution of anode temperature, saturated vapor pressure and vapor flux correspondingly, and the morphology of the anode melting pool has also the same deflection. Moreover, the anode center temperature and its gradient along the y direction decrease with the increase of deflection distance. On the contrary, the temperature of the anode side surface, toward which the heat flux density deflects, increases with increasing deflection distance. Related experiments also verify the correctness of the model and simulation results.